2015
DOI: 10.1097/brs.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Risk Factors for Neck Pain in the US Working Population

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 34 publications
4
22
0
7
Order By: Relevance
“…These results are consistent with those of Open Access previous studies. [6][7][8] Women are known to have a higher prevalence of NP/LBP and to be more susceptible to environmental risk factors than men. This might be due to their physical inactivity, lower bone mineral density and specific anatomical structure.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those of Open Access previous studies. [6][7][8] Women are known to have a higher prevalence of NP/LBP and to be more susceptible to environmental risk factors than men. This might be due to their physical inactivity, lower bone mineral density and specific anatomical structure.…”
Section: Open Accessmentioning
confidence: 99%
“…4 5 In addition, some studies have also indicated that occupational factors, including prolonged sedentary or office work hours, high work load/demands and inappropriate workstation designs, are associated with NP and/or LBP. [6][7][8] Sedentary or office workers in schools, hospitals and the military have been observed to have a high incidence and prevalence of NP and LBP. [9][10][11] This might be caused by their prolonged sitting time and specific body postures, such as inappropriate neck or Risk factors of non-specific neck pain and low back pain in computerusing office workers in China: a crosssectional study Sunyue Ye, 1,2 Qinglei Jing, 2 Chen Wei, 1 Open Access low back flexion or rotation, as well as other workplace environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…While it varies from one epidemiological study to another, the mean prevalence has been reported as 37% (2). Simple conditions that are prone to accumulation such as mechanical stress, lack of muscle strength, officecomputer jobs, nonergonomic working environments, and long working hours result in neck pain being more frequently seen in middle age (3). Cervical vertebral X-ray is the most common diagnostic tool in this circumstance; however, most of the time, the findings and the complaints of the patients do not comply with one another (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain may be associated with age, gender, physical fitness, occupation, physically demanding work, and other factors. In a recent study by Yang et al (2) on work-related risk factors for neck pain in the US working population, the top occupational group with highest prevalence of neck pain was identified as military specific personnel. For military personnel, head supported mass (HSM) such as helmet and helmet mounted gears pose additional risks of neck injuries.…”
Section: Introductionmentioning
confidence: 99%